Impact of internet usage on consumer impulsive buying behavior of agriculture products: Moderating role of personality traits and emotional intelligence - Jie, Wei; Poulova, Petra; Haider, Syed Arslan; Sham, Rohana Binti (Frontiers in Psychology, 2022)
E-commerce has led to a significant increase in internet purchases. The marketing sector is very competitive these days, and marketers have a difficult task: understanding the behavior of their customers. Strategic marketing planning relies heavily on consumer behavior since the consumer acts as the user, buyer, and payer in that process. Consumers’ behavior changes in response to shifts in the factors that influence it. The purpose of this research is to show how Internet usage influence on consumer impulsive buying behavior of agriculture products through moderating role personality traits and emotional intelligence in China organic market. The data gathered in three months from January to March 2022, due to COVID-19 pandemic data was gathered through an online survey questionnaire sent by Chinese social media platforms including WeChat and an email address. The PLS-SEM technique and the SmartPLS software version 3.2.8 were used for data analyses. The result revealed that internet usage positively and significantly influences consumer impulsive buying behavior. Also, both moderator personality trait and emotional intelligence positively and significantly moderate the relationship between internet usage and consumer impulsive buying behavior. Lastly, theoretical and practical implications, and future directions were discussed.